Interaction Effects of Education and Farming Experience on the Technical Efficiency Gains from Palaycheck system Training in Northern Mindanao, Philippines - Poonon, Sheila; Cosrojas, Karen Debbie (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the interaction effects of education and farming experience on the technical efficiency gains from PalayCheck System training among rice farmers in Northern Mindanao, Philippines. Anchored on the concept of technical efficiency in agricultural economics, the study utilized Stochastic Frontier Analysis (SFA) to evaluate farmers’ ability to maximize output using available inputs and technologies. A mixed-methods sequential explanatory research design was employed using both quantitative and qualitative approaches. The study adopted a with-and-without impact assessment design involving 570 respondents composed of 285 PalayCheck trainees and 285 non-trainees from selected municipalities in Bukidnon, Misamis Oriental, Misamis Occidental, and Lanao del Norte. Quantitative data were gathered through a self-structured survey questionnaire and analyzed using descriptive statistics, Cobb-Douglas Stochastic Frontier Analysis, t-tests, and Propensity Score Matching (PSM) to minimize selection bias. Qualitative data were collected through Focus Group Discussions (FGDs) and Key Informant Interviews (KIIs) and analyzed thematically. Findings revealed that PalayCheck participation had a positive but statistically insignificant effect on technical efficiency. Education and farming experience also showed statistically insignificant relationships with technical efficiency, while the interaction effects between training participation and both education and farming experience were likewise insignificant. The results suggest that the effectiveness of the PalayCheck System does not vary according to farmers’ educational attainment or farming experience. The study further indicated that structural and institutional factors such as access to production inputs, irrigation, mechanization, credit, and extension services may exert stronger influences on technical efficiency than socio-demographic characteristics alone. The study recommends strengthening the implementation of the PalayCheck System through integrated support services, continuous mentoring, demonstration farms, and farmer-friendly extension approaches to improve rice productivity and farmer welfare. The study supports Sustainable Development Goal (SDG) 2 on Zero Hunger through the promotion of improved rice productivity and sustainable agricultural practices. It also aligns with SDG 4, SDG 8, and SDG 12 by supporting agricultural education, farmer productivity, and efficient resource utilization. The findings contribute to agricultural, socio-economic, and educational sustainability by supporting inclusive extension strategies and integrated crop management practices that may enhance farmer welfare and sustainable rice production.